Chemistry towards Biology-Instruct: Snapshot - Hricovíni, Miloš; Owens, Raymond J; Bak, Andrzej; Kozik, Violetta; Musiał, Witold; Pierattelli, Roberta; Májeková, Magdaléna; Rodríguez, Yoel; Musioł, Robert; Slodek, Aneta; Štarha, Pavel; Piętak, Karina; et al. (International journal of molecular sciences, 2022)
The knowledge of interactions between different molecules is undoubtedly the driving force of all contemporary biomedical and biological sciences. Chemical biology/biological chemistry has become an important multidisciplinary bridge connecting the perspectives of chemistry and biology to the study of small molecules/peptidomimetics and their interactions in biological systems. Advances in structural biology research, in particular linking atomic structure to molecular properties and cellular context, are essential for the sophisticated design of new medicines that exhibit a high degree of druggability and very importantly, druglikeness. The authors of this contribution are outstanding scientists in the field who provided a brief overview of their work, which is arranged from in silico investigation through the characterization of interactions of compounds with biomolecules to bioactive materials.
Keywords: biological chemistry; molecular interactions; chemical biology; targeting; proteins and nucleic acids; Molecular Biology; biomaterials; biomolecules; structure and dynamics; virtual screening; molekulární biologie; natural compounds